Tinjauan Yuridis Terhadap Konsep Desentralisasi Yang Ideal Bagi Negara Kesatuan Republik Indonesia - Sugita, I Made (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Abstract The issue of decentralization is also closely related to the vertical separation of powers, namely a proposition that explains the distribution of powers between various levels of government. This is related to the division of authority between central and regional government levels. In Indonesia there have been several regulatory changes related to regional government, which of course also have an impact on the pattern of division of authority between the central and regional governments. The aim of this research is to analyze the ideal concept of decentralization for the Unitary State of the Republic of Indonesia. This type of research is normative legal research, because this research examines statutory regulations, theories or doctrines, and conceptual thinking and previous research related to the object of study in this research. The results of this research show that the ideal decentralization concept for the Unitary State of the Republic of Indonesia is a combination of symmetry and asymmetry which is the right combination or is known as the Integrated Decentralization System concept. In this decentralization, regions have broad authority in terms of managing their household affairs, including planning, implementation and evaluation, which are given to the regions with complete authority. In this decentralization, the role of the central government is not completely absent, the central government continues to supervise certain limits. Keywords: Decentralization, Ideal, and the Unitary State of the Republic of Indonesia